(untitled) (Revista LIDER, 2020)
This paper analyzes the labor market transformation in Valparaiso metropolitan area, under the perspective of dualcity, determining the relationships between the changes on the social and spatial configuration of the city. We use a longitudinal analysis based on census data and household surveys. The results showed that new inequalities on the labor market are reflected in an increasingly territorially fragmentation and a segregated distribution of the population. These phenomena could have negative effects in terms of restriction of employment opportunities and poverty reproduction. These results differ from the dual-city requirements approach and suggest new ways of understanding and inquire the socio-territorial consequences of economic globalization in Latin American cities.